133k views
3 votes
How this 0=t2−t−2 become this 0=(t−2)(t+1)

User Laverne
by
6.2k points

1 Answer

3 votes

In order to t² - t -2 = 0 become into this (t - 2)(t + 1) = 0, we have to know that a polynomial of the form ax² + bx + c = 0 can be factored as a(x + r1)(x + r2) = 0, where r1 and r2 are the roots of the equation ax² + bx + c = 0 and we can find them using the Quadratic Formula.

Let's solve the equation step-by-step.

t² - t -2 = 0 has the form at² + bt + c = 0, so can be factored as a(t + r1)(t + r2) = 0. With a = 1, b = -1, and c = -2

Step 1. Use the Quadratic Formula to find the roots r1 and r2.

t = −b ± √b²−4ac/2a

t = -(-1) ± √(-1)²−4(1)(-2)/2(1)

t = 1 ± √1+8/2

t = 1 ± √9/2 where r1 = 1 + √9/2 and r2 = 1 - √9/2

Step 2. Calculate the roots r1 and r2

r1 = 1 + √9/2 = 2

r2 = 1 - √9/2 = -1

Step 3. Write the factored equation a(t + r1)(t + r2) = 0, with a = 1 and the values of r1 and r2 with opposite signs.

1(t - 2)(t + 1) = 0

(t - 2)(t + 1) = 0

User Mohamed Yousof
by
6.4k points